Updating boundary conditions for bridge structures using modal parameters. (1st October 2019) - Shi, Zhou; Hong, Yu; Yang, Shili
Highlights: Modal parameters for updating constraints of bridge boundary conditions proposed. Method expressed as optimization problem to iteratively minimize modal residuals. Weighted least squares, first order perturbations of eigenvalues and eigenvectors used to solve the problem. Successfully tested using PC beams of straddle type monorail in Chongqing City. Results provide a benchmark model for damage identification using modal parameters. Abstract: A method for updating the additional rotational and horizontal constraints of bridge boundary conditions using modal parameters is proposed. The updating method is expressed as an optimization problem whose main goal is to iteratively minimize modal parameter residuals between the analytical model and the actual bridge structure. The weighted least-square method is utilized for solving the problem, and first-order perturbations of eigenvalues and eigenvectors are introduced in order to improve efficiency. Corresponding programs for optimization have been written in the MATLAB software package. To validate the proposed method, a maglev railway girder finite element (FE) model was taken as a numerical example. The result shows that the additional boundary constraints of the girder have been successfully updated within just four to seven iterations through only the first few modal parameters. Meanwhile, the sensitivity study on noise shows fairly good robustness of the method. According to prestressed concrete (PC) beams of the straddle-type monorail transit system in Chongqing City, based on on-site natural vibration test results and FE model calculations, the additional torsional constraints stiffnesses were successfully updated. The updated FE model with additional torsional constraints can be a benchmark model for use in damage identification based on modal parameters.